(untitled) (RIAF. International Journal of Physical Activity, 2026)
Introduction: High-performance soccer demands psychological and volitional factors that determine performance, yet their evaluation in non-professional contexts is often overlooked. Objective: To conduct a comprehensive socio-psychological diagnosis of youth soccer players to evaluate levels of concentrated attention, motivational profiles, and volitional qualities. Materials and Methods: A study was conducted with 38 male athletes (under-21) from Guanajuato. The Toulouse-Pierón Test, the 10 Wishes Test, and the Volitional Traits Test were applied through quantitative and qualitative analysis. Results: Significantly deficient concentrated attention was identified (68.41% of the sample), along with high volitional development (78.9%) and motivation oriented toward personal and economic advancement (62.16%). Conclusions: The athletes compensate for cognitive limitations with strong willpower and extrinsic motivation. It is necessary to implement psycho-pedagogical intervention programs that strengthen attentional skills without neglecting the existing volitional capital.